Fermented camel milk prevents carbon tetrachloride induced acute injury in kidney of mice. Issue 2 (22nd May 2018) - Hamed, Houda; Gargouri, Manel; Boulila, Salha; Chaari, Fatma; Ghrab, Ferdaws; Kallel, Rim; Ghannoudi, Zied; Boudawara, Tahia; Chaabouni, Semia; Feki, Abdelfattah El; Gargouri, Ahmed
Abstract : Fermented milk is known to possess potent antioxidant activity. The present study was undertaken to assess the preventive effect of fermented camel milk (FCM) prepared using lactococcus lactis subsp. cremoris against CCl4 induced kidney damage in mice. Nephrotoxicity was induced in mice by a single dose of CCl4 (10 ml/kg 0·3% olive oil, ip). Female mice were pretreated daily with FCM for 15 d. Renal damage was associated with an increase in oxidative stress parameters (lipid peroxidation, protein carbonyl and changes in antioxidant enzyme activities and non-enzymatic antioxidant) and nephropathology markers. The renal injury induced by CCl4 was confirmed by the histological study of the CCl4 -intoxicated mice. Pretreatment with FCM significantly prevented renal dysfunction by reducing oxidative stress, while mice recovered normal kidney histology. Moreover, FCM prevented toxicity biomarker changes by reducing creatinine, urea, uric acid, lactate dehydrogenase (LDH) and electrolytes levels in plasma. These data indicate that FCM is efficient in inhibiting oxidative stress induced by CCl4, and suggests that the administration of this milk may be helpful in the prevention of kidney damage.